A history of inequality: Top incomes in Brazil, 1926–2015. (October 2018) - Souza, Pedro H.G.F.
Highlights: First analysis of top income shares in Brazil from 1926 to 2015. Concentration of income at the top follows a sine wave pattern. Changes correlate closely with political-institutional disruptions. "Tax-adjusted" Ginis suggest surveys overstate the recent decline in inequality. Abstract: This paper uses income tax tabulations to estimate top income shares in Brazil over the long run. Between 1926 and 2015, the concentration of income at the top remained very high, following a sine wave trend: top shares ebbed and flowed over time, frequently in tandem with political and institutional disruptions. There is some evidence in favor of Williamson's "missed leveling" hypothesis regarding the origins of Latin America's exceptionally high levels of inequality, but the recent decline in inequality is cast in a more dubious light, since top income shares remained quite stable since 2000 and the "tax-adjusted" Gini coefficients show a smaller and shorter, though still sizeable, decrease. The nature of the political regime matters, but democracy is not a sufficient condition for redistribution. Brazil's tumultuous political history suggests top income shares change substantially mostly during political-institutional crises, when the typical quid pro quo of more liberal regimes in normal times collapses. I complement the analysis with international comparisons and a discussion of the role of institutions in shaping inequality.